Kepemimpinan Dalam Keluarga: Perspektif Fiqh dan Analisis Gender - Maulana, Bani Syarif (Musawa Jurnal Studi Gender dan Islam, 2004)
Islam is a religion which has attempted to elevate the status of women so that there should be no discrimination between women and men from the Islamic perspective. However, in some fiqh texts, which are based on selected Qur'an and hadith, there is discrimination against women. On the other side, gender discourse now becomes an important issue and is used to improve the status of women. This article attempts to explore both the jiqh texts and gender discourse on the models of leadership in a family, especially on the role of women and men in the family and on the sexual relations, from the Islamic perspective.